New material and phylogenetic position of Arenysaurus ardevoli, a lambeosaurine dinosaur from the late Maastrichtian of Arén (northern Spain) - Cruzado Caballero, Penélope (2013)
Fil: Cruzado Caballero, Penélope. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina